Yield performance of lentil as a mixed crop with rapeseed (Bangladesh Agronomy Journal, 2015)
Mixed crop cultivation of lentil and rapeseed could be a promising technology for yield maximization. The field experiment was carried out at multilocation testing site, Kashinathpur, Pabna during the rabi season of 2011-12 and 2012-13 to verify the performance of rapeseed as mixed crop with lentil at different seeding ratios. The treatment comprises for the experiment were T1: Sole lentil (100%), T2: Sole rapeseed (100%), T3: Lentil (100%) + Rapeseed (10%), T4: Lentil (100%) + Rapeseed (20%), T5: Lentil (100%) + Rapeseed (30%) and T6 :Farmers practice :Lentil (100%) + Rapeseed (15%). The highest lentil equivalent yield (2.22 t ha-1 in and 2.48 ) and maximum land equivalent ratios (1.27 and 1.28) were observed in T4 treatment in 2011-12 and 2012-13, respectively.. It was noted that all the mixed cropping systems produced higher equivalent yield and LER than that of their corresponding sole crops. . Cost and return analysis showed that the highest net return (Tk. 127774 ha-1) was found in T4 treatment while sole rapeseed gave the lowest net return (Tk. 60540 ha-1). Net return was always higher under mixed cropping system than that of sole cropping. The highest benefit cost ratio 3.48 was recorded from Lentil (100%) + Rapeseed (20%) where as the minimum (1.39) from soli rapeseed.Bangladesh Agron. J. 2014, 17(1): 33-40